Human capital transformation as mediator between love for knowledge and excellent Muslim - Syaidatun Nazirah Abu Zahrin,; Shamila Abu Hasan,; Mohamad Zaki Samsudin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Transformation of human capital plays an important role as mediator between love for knowledge and Excellent Muslim personality. One of the most important ways to transform human capital is to improve the education system. This study was conducted to model out the role of transformation of human capital as mediator for the relationship between love for knowledge and Excellent Muslim personality. The study was conducted among 767 students of an Institute of Higher Education around the Klang Valley, Malaysia. Structural Equation Modelling (SEM) was used to analyse the structural relationships between love for knowledge, transformation of human capital and Excellent Muslim personality, which analysed the measured variables and latent constructs to indicate the causal flow of the relationships. A significant partial mediating role of Human Capital Transformation (Transformasi Modal Insan TMI) was found between perceived Love for Knowledge (Cinta Ilmu CI) and Excellent Muslim personality (Muslim Cemerlang MC) respectively. Results obtained also shows that the strength of the relationships that occur between CI and MC is partially mediated by the existence of TMI. This indicates that the presence of Human Capital Transformation significantly reinforces the relationship of Love for Knowledge and Excellent Muslim personality.